Ash'ariyah and Maturidiyah: History, Main Teachings, and Comparison with Mu'tazilah - Sari Nur Khasanah; Muhammad Syukri Azizi; Ekawati Ekawati (Penerbit Hellow Pustaka, 2025)
This article aims to comprehensively examine the theological schools of Ash'arism and Maturidism, along with their relationship to Mu'tazilite thought. Ash'arism and Maturidism emerged as responses to the extreme rationalism promoted by the Mu'tazilites. Both schools offer a balanced approach between reason and revelation, with Ash'arism prioritizing scriptural authority and Maturidism granting a greater role to rational inquiry within the boundaries of Sunni orthodoxy. This study employs a qualitative-descriptive method using a library research approach based on both classical and contemporary literature. The findings reveal that, although Ash'arism and Maturidism share the same Sunni foundations, they differ significantly in their epistemological emphasis and doctrinal details. This article highlights key similarities and differences among the three schools, particularly regarding the nature of God, human free will, the createdness of the Qur’an, and ethical reasoning. It is hoped that this study contributes to the strengthening of a moderate Islamic theology that is both faithful to revelation and responsive to contemporary challenges.